Trigonometry! #50

Geometry Level 3

If α + β γ = π \alpha+\beta-\gamma=\pi then sin 2 α + sin 2 β sin 2 γ \sin^{2} \alpha + \sin^{2} \beta - \sin^{2} \gamma is equal to which of the following?

This problem is part of the set Trigonometry .

sin α sin β cos γ \sin \alpha \sin \beta \cos \gamma 2 sin α sin β cos γ 2\sin \alpha \sin \beta \cos \gamma 2 cos α cos β sin γ 2\cos \alpha \cos \beta \sin \gamma cos α cos β sin γ \cos \alpha \cos \beta \sin \gamma

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

You may magnify the above file.

sin 2 θ cos 2 ϕ = sin 2 θ sin 2 θ sin 2 ϕ . . . . . . ( 1 ) γ = ( α + β ) π cos γ = cos ( α + β π ) = cos { ( α + β ) ( 1 ) + 0 } cos γ = cos ( α + β ) . . . . . . . . . . ( 2 ) sin γ = sin { ( α + β ) π } = sin ( α + β ) ( cos π ) 0 sin γ = { sin α cos β + cos α sin β } sin 2 γ { u s i n g ( 1 ) f o r sin 2 α cos 2 β a n d sin 2 α cos 2 β } = sin 2 α cos 2 β + cos 2 α sin 2 β + 2 sin α sin β ( cos α cos β ) = sin 2 α + sin 2 β 2 sin 2 α sin 2 β + 2 sin α sin β cos α cos β = sin 2 α + sin 2 β 2 sin α sin β ( sin α sin β cos α cos β ) = sin 2 α + sin 2 β + 2 sin α sin β cos ( α + β ) = sin 2 α + sin 2 β 2 sin α sin β cos γ . . . . . . f r o m ( 2 ) sin 2 α + sin 2 β sin 2 γ = sin 2 α + sin 2 β { sin 2 α + sin 2 β 2 sin α sin β cos γ } 2 sin α sin β cos γ \sin^2\theta\cos^2\phi =\sin^2\theta-\sin^2\theta\sin^2\phi......(1)\\ \gamma=(\alpha+\beta)-\pi \\ \cos \gamma= \cos( \alpha+\beta~~-~~\pi) =\cos\{(\alpha+\beta)(-1) +0\} \\\therefore~\cos \gamma=-\cos(\alpha+\beta) ..........(2) \\ \sin \gamma= \sin\{(\alpha+\beta)-\pi \} =\sin(\alpha+\beta)(\cos \pi)-0 \\ \therefore~\sin \gamma=-\{\sin\alpha\cos\beta +\cos\alpha\sin\beta\} \\ \therefore~\sin^2 \gamma ~~\{using ~~(1)~for~\sin^2\alpha\cos^2\beta ~and~\sin^2\alpha\cos^2\beta \}\\~~~~= \sin^2\alpha\cos^2\beta +\cos^2\alpha\sin^2\beta + 2\sin\alpha\sin\beta(\cos\alpha\cos\beta)\\ ~~~~=\sin^2\alpha+\sin^2\beta-2 \sin^2\alpha\sin^2\beta+2\sin\alpha\sin\beta\cos\alpha\cos\beta \\~~~~=\sin^2\alpha+\sin^2\beta -2\sin\alpha\sin\beta(\sin\alpha\sin\beta-\cos\alpha\cos\beta)\\~~~~ =\sin^2\alpha+\sin^2\beta+2\sin\alpha\sin\beta\cos(\alpha+\beta) \\~~~~=\sin^2\alpha+\sin^2\beta-2\sin\alpha\sin\beta\cos\gamma......from (2)\\ \color{#20A900}{\therefore~\sin^{2} \alpha + \sin^{2} \beta - \sin^{2} \gamma\\~~~~=\sin^{2} \alpha + \sin^{2} \beta - \{\sin^{2} \alpha + \sin^{2} \beta - 2\sin\alpha\sin\beta\cos\gamma\} }\\ ~~~~~~~~\boxed {\color{#D61F06}{2\sin\alpha\sin\beta\cos\gamma} }

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...